The Effect of Lecturer Professionalism And Teaching Motivation on Lecturers Strengthening The Nation's Competitiveness (Survey on XYZ College Lecturers in Central Jakarta City) - Khasanah Khasanah (ADI Journal on Recent Innovation, 2020)
The purpose of this study was to determine the effect of Lecturer Professionalism and Motivation Teaching Lecturers equally against National Competitiveness in Higher Education XYZ in Central Jakarta. The research method used was a survey with correlation analysis and regression. Data on lecturer professionalism, teaching motivation, and national competitiveness obtained through a questionnaire compiled by researchers, namely those that measure things related to the three things above. The results showed: 1) There was an influence significant independent variable lecturer professionalism and lecturer teaching motivation together with the dependent variable of the nation's competitiveness. This is proven by the results of testing hypothesis through multiple regression analysis that the value of Sig = 0,000 and Fcount = 27,746, whereas F table = 3.25 so that the Sig value <0.05 and Fcount> F table which means the regression is significant. 2) There is a significant influence of the lecturer professionalism independent variable on the variable nation's competitiveness. This is evidenced by the results of testing the hypothesis obtained that the value Sig = 0.001 and tcount = 3.808, while table = 1.68 so the value of Sig <0.05 and tcount> table which means there is a significant influence. 3) There is a significant influence of variables free motivation to teach the nation's competitiveness variable. This is proven by the results Hypothesis testing obtained that the value of Sig = 0.001 and tcount = 3.772, while table = 1.68 so that the Sig value <0.05 and tcount> t table which means that there is an influence significant. The equation shows that there is an influence of professionalism lecturer on the nation's competitiveness.